3 Cases of Acute necrotizing encephalopathy,is this an epidemic or just an incidental? - Ahmadabadi, Farzad; Ruhollahi, Sonia; Maskani, Reza; Jafari, Narjes; Karimi Dardashti, Sanaz (Iranian Journal of Child Neurology, 2020)
Acute necrotizing encephalopathy of childhood (ANEC) is a disease characterized by post infectious (respiratory or gastrointestinal) encephalopathy accompanying with fever and rapid alteration of consciousness and seizures. Acute encephalopathy following viral infection with seizure and altered of consciousness and absence of CSF pleocytosios with occasional increased level of protein are clinical characteristics of ANEC (1). This disease is nearly exclusively in East Asian infants and children who had been previously healthy (2). Serial magnetic resonance imaging examinations have demonstrated symmetric lesion involving the thalami, brainstem, cerebellum, and white matter in this disease (8). The condition accompanies a poor prognosis with high morbidity and mortality rates. We introduce 3 cases with ANE those referred to our hospital during 2 weeks and created this idea that we have an epidemic.